Subsistence strategies in traditional societies distinguish gut microbiomes - Obregon-Tito, Alexandra J.; Tito, Raul Y.; Metcalf, Jessica; Sankaranarayanan, Krithivasan; Clemente, Jose C.; Ursell, Luke K.; Zech Xu, Zhenjiang; Van Treuren, Will; Knight, Rob; Gaffney, Patrick M.; Spicer, Paul; Lawson, Paul; et al. (Nature communications, 2015)
Recent studies suggest that gut microbiomes of urban-industrialized societies are different from those of traditional peoples. Here we examine the relationship between lifeways and gut microbiota through taxonomic and functional potential characterization of faecal samples from hunter-gatherer and traditional agriculturalist communities in Peru and an urban-industrialized community from the US. We find that in addition to taxonomic and metabolic differences between urban and traditional lifestyles, hunter-gatherers form a distinct sub-group among traditional peoples. As observed in previous studies, we find that Treponema are characteristic of traditional gut microbiomes. Moreover, through genome reconstruction (2.2–2.5 MB, coverage depth × 26–513) and functional potential characterization, we discover these Treponema are diverse, fall outside of pathogenic clades and are similar to Treponema succinifaciens , a known carbohydrate metabolizer in swine. Gut Treponema are found in non-human primates and all traditional peoples studied to date, suggesting they are symbionts lost in urban-industrialized societies. The gut microbiomes of urban-industrialized societies differ from those of traditional rural societies and hunter-gatherers. Here the authors perform a comparative analysis of available and new gut microbiome data to provide fresh insight into these differences.